Indication and Technical Aspects of Adrenal Blood Sampling - Blondin, D.; Quack, I.; Haase, M.; Kücükköylü, S.; Willenberg, H. S. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Adrenal disorders are relative frequent with regard to the incidence of adrenal tumors and the high portion in causes of secondary hypertension. Morphological changes in the adrenal glands can lead to very different functional disorders that may be clinically overt or hard to diagnose. On the other hand, they can already be functionally relevant when structural changes are too small to be picked up by imaging. Adrenal venous sampling serves to determine the source of hormone excess through the analysis of adrenal blood. In this manuscript, we call attention to the clinical backgrounds, critical points in praxis, technical aspects and developments in the the field of adrenal venous sampling. The consideration of these important points in the clincal setting may make adrenal vein sampling studies sucessful and help to select patients that qualify for adrenalectomy.Key Points:• Selective adrenal venous sampling (AVS) currently continues to be the gold standard for localization diagnostics in patients with primary hyperaldosteronism.• Comprehensive standardization of all preceding examinations and AVS is necessary to ensure high success rates.• The method is supported by contrast-enhanced imaging for ensuring proper positioning of the catheter in the adrenal veins and the rapid cortisol assay.• Knowledge of the anatomy and normal variants of the adrenal veins facilitates adrenal venous sampling.Citation Format:• Blondin D, Quack I, Haase M et al. Indication and Technical Aspects of Adrenal Blood Sampling. Fortschr Röntgenstr 2015; 187: 19 – 28
Keywords: abdomen; adrenal gland; angiography; endocrine disorders